2021
DOI: 10.3389/fonc.2021.715020
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Outcome of PSMA-PET-Based Dose-Escalated Salvage Radiotherapy Versus Conventional Salvage Radiotherapy for Patients With Recurrent Prostate Cancer

Abstract: IntroductionProstate-specific membrane antigen-positron emission tomography-(PSMA-PET) imaging facilitates dose-escalated salvage radiotherapy (DE-SRT) with simultaneous-integrated boost (SIB) for PET-positive lesions in patients with prostate cancer (PC). Therefore, we aimed to compare toxicity rates of DE-SRT with SIB to conventional SRT (C-SRT) without SIB and to report outcome.Materials and MethodsWe evaluated 199 patients who were treated with SRT between June 2014 and June 2020. 101 patients received DE-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…One such role is radiation boost to imaging-identified positive lesions. This approach allows for the delivery of high radiation doses to the recurrent lesions without increasing the dose to normal tissues 29–31 . In view of this improved dose delivery to PCa recurrence lesions without increasing normal tissue toxicity from molecular imaging-guided radiotherapy boosting, patients in another ongoing trial (NCT03762759) receive a total of 64.8 to 70.2 Gy at 1.8 Gy per fraction to the prostate bed with a boost to 70.2 to 76.0 Gy to areas of radiotracer uptake on PET/CT imaging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One such role is radiation boost to imaging-identified positive lesions. This approach allows for the delivery of high radiation doses to the recurrent lesions without increasing the dose to normal tissues 29–31 . In view of this improved dose delivery to PCa recurrence lesions without increasing normal tissue toxicity from molecular imaging-guided radiotherapy boosting, patients in another ongoing trial (NCT03762759) receive a total of 64.8 to 70.2 Gy at 1.8 Gy per fraction to the prostate bed with a boost to 70.2 to 76.0 Gy to areas of radiotracer uptake on PET/CT imaging.…”
Section: Discussionmentioning
confidence: 99%
“…This approach allows for the delivery of high radiation doses to the recurrent lesions without increasing the dose to normal tissues. [29][30][31] In view of this improved dose delivery to PCa recurrence lesions without increasing normal tissue toxicity from molecular imaging-guided radiotherapy boosting, patients in another ongoing trial (NCT03762759) receive a total of 64.8 to 70.2 Gy at 1.8 Gy per fraction to the prostate bed with a boost to 70.2 to 76.0 Gy to areas of radiotracer uptake on PET/CT imaging. The results of this trial, when concluded, will advance knowledge regarding the comparative impact of these 2 imaging modalities on FFS post-SRT in men who are diagnosed with PCa recurrence post-RP.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a recent search on https://www.clinicatrials.gov only identified NCT05328505 and NCT01411345. At the moment, the clinical experience is also limited and mostly retrospective [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] . A similar approach was used in the recent phase 2, dual-center, open-label, single-arm SCIMITAR trial, testing extreme hypofractionation in patients with biochemical and/or clinical relapse [45] .…”
Section: Discussionmentioning
confidence: 99%
“…Vogel et al. ( 20 ) used a simultaneous-integrated boost for PSMA-PET-positive lesions to 76.5 Gy in 2.25 Gy vs. 68 Gy in 2 Gy fractions. They found a better PSA-response rate for patients treated with dose-escalation.…”
Section: Do We Need To Increase the Dose In Postoperative Radiotherap...mentioning
confidence: 99%